1995
DOI: 10.1128/jb.177.5.1233-1238.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of MgtE, a putative new class of Mg2+ transporter from Bacillus firmus OF4

Abstract: The MM281 strain of Salmonella typhimurium which possesses mutations in each its three known Mg 2؉ transport systems and requires 100 mM Mg 2؉ for growth was used to screen a genomic library from the gram-positive alkaliphilic bacterium Bacillus firmus OF4 for clones that could restore the ability to grow without Mg 2؉ supplementation. . Mutant strains lacking a functional CorA transporter demonstrate a significant reduction in the ability to take up Mg 2ϩ as well as increased resistance to the cytotoxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 23 publications
1
100
0
1
Order By: Relevance
“…Clearly, SLC41A1 does not have the same cationic specificity as MgtE (16,17 Quantitative RT-PCR analysis was performed with SLC41A1 mRNA purified from the indicated tissues derived from mice maintained on a normal (0.5% by weight) or low-Mg 2ϩ (Ͻ0.01%) diet for 5 days. Mouse SLC41A1 and murine ␤-actin RNA were measured with real-time RT-PCR (AB7000, Applied Biosystems) using primers designed to mouse SLC41A1 and ␤-actin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, SLC41A1 does not have the same cationic specificity as MgtE (16,17 Quantitative RT-PCR analysis was performed with SLC41A1 mRNA purified from the indicated tissues derived from mice maintained on a normal (0.5% by weight) or low-Mg 2ϩ (Ͻ0.01%) diet for 5 days. Mouse SLC41A1 and murine ␤-actin RNA were measured with real-time RT-PCR (AB7000, Applied Biosystems) using primers designed to mouse SLC41A1 and ␤-actin.…”
Section: Discussionmentioning
confidence: 99%
“…Computer analysis of the SLC41A1 protein structure reveals that it comprises 10 putative transmembrane domains, 2 of which are highly homologous to the integral membrane part of the prokaryote MgtE protein family. MgtE was initially identified in the bacteria Providencia stuartii and Bacillus firmus by Smith, Maguire, and their colleagues in their search for members of the CorA (cobalt resistance) family of Mg 2ϩ uptake transporters (15)(16)(17). On the basis of the similarity of SLC41A1 to MgtE, Wabakken et al (19) suggested that the human solute carrier SLC41A1 may be a eukaryotic Mg 2ϩ transporter.…”
mentioning
confidence: 99%
“…Clearly, cationic specificity was not the same for the SLC41 transporters as for MgtE (140). For example, SLC41A1 does not transport Co 2ϩ to any degree, and Ni 2ϩ is not a selective inhibitor of Mg 2ϩ transport.…”
Section: Strategy For Identifying Novel Mg 2؉ Transportersmentioning
confidence: 99%
“…The identification and characterization of plant, prokaryote, and yeast Mg 2ϩ transporters have been extensively reviewed elsewhere (35,70,73,138 transport (30,36,87,93,98,105,168). CorA is the primary Mg 2ϩ uptake transporter in most prokaryotes (140). It is constitutively expressed in bacteria and does not respond to external Mg 2ϩ levels (70).…”
mentioning
confidence: 99%
“…Its Mg 2ϩ -transporting activity was demonstrated by a complementation assay and the uptake of a Co 2ϩ isotope in vivo (9). In bacteria, translation of its gene is regulated by a Mg 2ϩ -specific riboswitch (10).…”
mentioning
confidence: 99%